Review of the Fund's Mandate : Follow-Up on Modernizing Surveillance. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2010)
The paper reviews the adequacy of the Fund's precautionary balances and proposes a more transparent and rules-based framework for adjusting the precautionary balance target through time. The framework seeks to provide sufficient flexibility to capture the main elements considered relevant by the Board in the past when setting the target and draws on approaches followed by other IFIs, adapted to the particular circumstances of the Fund.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Fund Surveillance; Policy; PP; Staff; United Kingdom